Conversion of bioethanol over zeolites; Chemical Engineering Journal; Vol. 154, iss. 1-3 : XVIII International Conference on Chemical Reactors - CHEMREACTOR -18 (September 29 - October 3, 2008, Malta) — CHEMREACTOR - 18 - Makarf Yu. I. Yusuf Isa; Yakimova M. S. Marina Sergeevna; Lermontov A. S. Anatoly Sergeevich; Erofeev V. I. Vladimir Ivanovich; Koval L. M. Lubov Mikhailovna; Tretiyakov V. F. Valentin Filipovich (2009, 2009)
Title screen